To Evaluate Magnetic Resonance Imaging’s (MRI) Diagnostic Accuracy in the Pre-Operative Assessment of Peri-Anal Fistula - Baloch, Zakia; Nizam, Shaista (Indus Journal of Bioscience Research, 2025)
Introduction: Because a misdiagnosis could result in a recurrence of the disease or potential surgical side effects including fecal incontinence, the goal of this study was to precisely detect and describe the perianal fistula and assist surgeons in selecting the optimal surgical treatment. Study design: Cross-sectional (validation) study. Settings: Radiology department of JPMC, Karachi. Methodology: The study comprised 269 patients aged 18 to 70 years presenting to the radiology department of JPMC, Karachi, and who had frequent anal pain and swelling around anus with bowel movements. The study excluded patients with recurrent peri-anal disease, those who had undergone surgery, those who were on anti-inflammatory medications for any reason, and those who had undergone surgery. The 1.5 Tesla system (GE HDXT medical system) was used to examine every patient in the MR unit. The MRI results were not disclosed to the surgeon, and the surgical findings were compared for PAF. The outcomes were verified and compared to the surgical results. Results: MRI sensitivity was (94.05%), specificity (86.14%), PPV (91.86%), NPV (89.69%), and diagnostic accuracy (91.08%) in the pre-operative evaluation of peri-anal fistula. Conclusion: According to the study’s findings, MRI is an extremely sensitive and precise imaging technique for pre-operative evaluation of peri-anal fistula.